Study on the awareness of consumer relating to landfilling as a waste disposal alternative [electronic resource] - 179925 Semsassom Abdullah; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2007